2013
DOI: 10.1352/1944-7558-118.5.353
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Factors Influence Visual Search for Meaningful Symbols in Individuals With Intellectual Disabilities and Down Syndrome or Autism Spectrum Disorders

Abstract: Augmentative and alternative communication (AAC) systems often supplement oral communication of individuals with intellectual and communication disabilities. Research with nondisabled preschoolers has demonstrated that two visual perceptual factors influence speed and/or accuracy of finding a target - the internal color and spatial organization of symbols. Twelve participants with Down syndrome and 12 with ASD underwent two search tasks. In one, the symbols were clustered by internal color; in the other the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Wilkinson and McIlvane showed that children with ASD performed better with the colour‐based clustering method in search and match experiments rather than specifying one colour in a pattern. A case has also been reported linking colour‐processing differences to obsession and phobia .…”
Section: Visual Impairments In Asdmentioning
confidence: 99%
“…Wilkinson and McIlvane showed that children with ASD performed better with the colour‐based clustering method in search and match experiments rather than specifying one colour in a pattern. A case has also been reported linking colour‐processing differences to obsession and phobia .…”
Section: Visual Impairments In Asdmentioning
confidence: 99%
“…as aaC apps rapidly evolve, studies are needed to evaluate the efficacy of these apps and to compare mobile aaC apps and more traditional aaC systems . in addition, although SGDs have frequently presented icons in grid array formats (Wilkinson & Mcilvane, 2013), newer formats, such as visual scene displays, have been introduced. These displays use contextual scenes in the form of photographs or drawings to present in-context concepts (Wilkinson & Jagaroo, 2004).…”
Section: Expansion Of Research In Mobile Technologiesmentioning
confidence: 99%
“…Previous research (Wilkinson & McIlvane, 2013;Wilkinson, O'Neill, & McIlvane, 2014;Liang et al, 2018) has demonstrated that the different conditions presented participants with varied cognitive-perceptual requirements (Figure 1). In the control condition, only one symbol was shown, requiring neither memory of the previously displayed stimulus nor visual scanning of competing stimuli.…”
Section: Introductionmentioning
confidence: 96%